The foot in systemic disease: management of the patient with rheumatoid arthritis or diabetes mellitus. Issue 4 (August 2019) - Walker, Roland; Wong, Fabian; Singh, Sam; Ajuied, Adil
Abstract: The foot is commonly affected in systemic diseases such as rheumatoid arthritis and diabetes mellitus. Treating patients who suffer with foot pathology secondary to systemic diseases requires a multidisciplinary approach, following the principles outlined within this review. There is little high level evidence in this field, such as prospective controlled clinical trials, hence much of what we know and practise is based upon the expert opinion of key individuals in specialist centres, to whom we owe a great debt.